INFLUENCE OF AFLOTOXIN B1 ON PROTEIN AND DNA CONTENT OF LYMPHOID ORGANS OF ONE WEEK OLD BROILERS DURING INDUCED AFLOTOXICOSIS - P. J. R. NATHANAEL; S. LALITHA KUMARI; V. VIVEKA VARDHANI (The Bioscan, 2010)
Metabolic exudates liberated by Aspergillus flavus and Aspergillus parasiticus are referred as mycotoxins. Among them Aflotoxin B1 (AFB1) is prominent and is categorized as the group 1 carcinogen along with its mutagenic and terrotogenic behavior. AFB1 is hepatotoxic, nuerotoxic, and nephrotoxic causing a high degree of immunosupression in poultry birds having a broad spectrum of lethal impact as carcinogenic, hepatotoxic, mutagenic, and nephrotoxic agent. Our present investigation is focused on determining the levels of protein and DNA in bursa fabricus and cecal tonsils of one week old broilers suffering due to induced chronic aflotoxicosis thereby to know the intensity of alterations and anomaly of cellular mechanisms and to understand the immune response of the individual in the light of its physiological state. The organs that are playing a pivotal role are highly affected by AFB1 which causes adverse and disturbed levels of protein and DNA. Alterations in the metabolism of proteins in bursa fabricus and cecal tonsils of broilers treated with AFB1 are the significant toxic effects of AFB1.